Territorial Brands for Rural Development Strategies in Protected Natural Spaces: A Social Demand Analysis - José A. Albaladejo-García; Gonzalo Martínez-García; José M. Martínez-Paz (Land)
The economic decline of some rural areas is leading to the development of strategies to enhance the value of local economies. This is particularly important in protected natural spaces, where the aim is to encourage the provision of ecosystem services and strengthen commitment to sustainable development and economic growth. One of the rural development strategies with a growing interest in promoting the sustainability of rural areas in protected natural spaces is the use of territorial brands. The objective of this work is to analyse the social demand for territorial-branded products in protected natural spaces. The territorial brand of Sierra Espuña Regional Park (southeastern Spain) was selected as a pragmatic case, with the aim of promoting the production and consumption of sustainable local products. To this end, a contingent valuation survey of consumers was carried out to study the demand for honey, one of the most characteristic products of this territorial brand. The results demonstrate the high social demand for honey under the Sierra Espuña Territorial Brand, with an average surcharge of almost thirty percent compared to the conventional product, and a positive influence of the perception of supporting ecosystem services on this social demand. These results provide an empirical basis for the integration and promotion of production and marketing strategies with territorial brands, in the interests of rural development from and for the territory.